The performance of Mpwapwa breed cattle under small holder dairy farmer management in a rural area - Kasonta, J.S.; Mkonyi, J.I. (1991)
In the years 1987-1988, twenty Mpwapwa in-calf heifers and six bulls were sold to individual farmers of Berege willage in Mpwapwa district, Dodoma region. After calving, most cows produced on average about four liters of milk per day of lactation, beside the milk suckled by the calf. This production level is about three times higher than that of indigenous zebu cows under comparable management. Also, Mpwapwa calves were observed to grow much faster than calves of indigenous cattle. So far, no significant losses have been reported due to diseases or other environmental stress factors. At present there are about 50 Mpwapwa breed cattle at Berege. Therefore there is an urgent need of introducing an appropriate breeding programme for the herd in order to avoid the increased possibility of inbreeding and to facilitate a wider disribution of the improved zebu type of cattle to farmers in need of them.